Author Package, TPPS, Vol. 7 (2022) - Tabarzad, Maryam (Trends in Peptide and Protein Sciences, 2023)
The Trends in Peptide and Protein Sciences is a peer-reviewed, online-only (previously print-online), scientific journal owned by Protein Technology Research Center, Shahid Beheshti University of Medical Sciences and documents in all important aspects of the research in peptides and proteins focusing on analytics and impurities, bioinformatics, biopharmaceuticals and vaccines, biotechnology, chemical synthesis, conformational analysis, design and development of protein therapeutics, determination of structure, enzymology, folding and sequencing, formulation and stability, function, genetics, immunology, kinetics, modeling, molecular biology, pharmacokinetics and pharmacodynamics of therapeutic proteins and antibodies, pharmacology, protein engineering and development, protein-protein interaction, proteomics, purification/expression/production, simulation, thermodynamics and hydrodynamics and protein biomarkers. The aim of this Journal is to publish high quality original research articles, reviews, short communications and letters and to provide a medium for scientists and researchers to share their findings from the area of peptides and proteins. The Trends in Peptide and Protein Sciences is published in collaboration with Iranian Association of Pharmaceutical Scientists. From volume 3 (2018) of TPPS, articles are continuously published online only, as soon as the review process is completed.